Impact of leadership styles on creative deviance: mediating roles of feedback-seeking and psychological availability, with moderating effects of achievement motivation and learning climate - Cui, Haojing; Wang, Jia-Fure (Edelweiss Applied Science and Technology, 2025)
Innovation becomes vital to organizational competitiveness, and stimulating employees' creative deviations has emerged as a key management challenge. This study investigates the impact of dual leadership—open and closed styles—on creative deviations, focusing on the mediating roles of feedback-seeking behavior and psychological availability and the moderating effects of achievement motivation and organizational learning climate. The survey collected data from 635 employees in high-tech and creative industries; the findings reveal that open leadership promotes creative deviations by enhancing feedback-seeking behavior and psychological availability. In contrast, closed leadership has the opposite effect. Achievement motivation strengthens the positive effects of open leadership and mitigates the negative impacts of closed leadership. Additionally, an organizational learning climate enhances feedback-seeking behavior and psychological availability, further supporting creative deviations. These insights guide organizations in optimizing leadership styles and work environments to unlock employees' innovative potential.